PENGARUH PEMAHAMAN ALKITAB DEWASA SEBAGAI DASAR PANGGILAN PELAYANAN KEMAJELISAN DI GEREJA KRISTEN JAWA SELOKATON - GAWA, MAHENDRA YONATAN EDO; WENING, SRI (ACADEMIA: Jurnal Inovasi Riset Akademik, 2024)
Understanding the Bible is one of the most important services to be carried out in improving the spiritual quality of the congregation. Apart from that, understanding the Bible in the church is very helpful in the church's task of increasing interest in congregational services. This research aims to find out the influence of mature Bible understanding on the call to ministry to the assembly in Selokaton Javanese Christian Church, after processing data using SPSS and it is known that there is a significant influence of adult understanding of the Bible as the basis for the call to assembly service at the Selokaton Javanese Christian Church. By looking at the correlation table, it shows the magnitude of the relationship between the independent variable and the dependent variable. It can be seen from the correlation coefficient column that it is 0.912. Based on the correlation coefficient interpretation guidelines according to Sugiyono, this shows a strong correlation with criteria between 0.60 - 0.912. In this way, understanding the Bible really helps the church in increasing the congregation's interest in ministry. Therefore, it is hoped that members of the congregation will feel that mature understanding of the Bible is the basis for the calling of ministers at the Selokaton Javanese Christian Church. ABSTRAKPemahaman Alkitab merupakan salah satu pelayanan yang sangat penting untuk dilaksanakan dalam meningkatkan kualitas kerohanian jemaat, selain itu pemahaman Alkitab yang ada di dalam gereja sangatlah membatu tugas gereja dalam meningkatkan minat pelayanan jemaat. Penelitian ini bertujuan untuk mengetahui bagimana pengaruh pemahaman Alkitab dewasa terhadap panggillan pelayanan kemajelisan di Gereja Kristen Jawa Selokaton, setelah melakukan pengolahan data menggunakan spss dan diketahui bahwa terdapat pengaruh yang signifikan dari pemahaman Alkitab dewasa sebagai dasar panggilan pelayanan kemajelisan di Gereja Kristen Jawa Selokaton. Dengan melihat table korelasi menunjukan besar hubungan variable bebas terhadap variable terikat. Terlihat dari kolom koefisien korelasinya sebesar 0,912. Berdasarkan pedoman interpretasi koefisien korelasi menurut Sugiyono, hal ini menunjukkan keeratan yang kuat dengan kriteria antara 0,60 – 0,912. Dengan demikian Pemahaman Alkitab sangatlah membantu gereja dalam meningkatkan minat pelayanan jemaat. Oleh karena itu diharapkan warga jemaat merasakan bahwa pemahaman Alkitab dewasa adalah dasar panggilan pelayan di Gereja Kristen Jawa Selokaton.